2021
DOI: 10.21203/rs.3.rs-612351/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver Stiffness Assessed by Real-Time Two-dimensional Shear Wave Elastography Predicts Hypersplenism in Patients with Wilson’s Disease: A Prospective Study

Abstract: Background To explore the value of liver stiffness assessed by two-dimensional real-time shear wave elastography (2D-SWE)in predicting the occurrence of hypersplenism in patients diagnosed with Wilson’s disease (WD). Methods A total of 90 WD patients were enrolled in this prospective study between May 2018 and December 2018. Clinical data and ultrasound imaging including 2D-SWE liver stiffness of WD patients as baseline data were collected. Patients were followed up for 24 months, or patients developed hypersp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Moreover, the predictive model is moderate, with an accuracy of 0.58 [13]. Wang et al found that liver stiffness evaluated by two-dimensional real-time shear wave elastography, whose inflection point was 10.45 kPa, could predict the occurrence of hypersplenism [14]. Another study found that acoustic radiation force impulse and fibrosis-4 could be used to distinguish cirrhosis in patients with WD, which could partly replace liver biopsy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the predictive model is moderate, with an accuracy of 0.58 [13]. Wang et al found that liver stiffness evaluated by two-dimensional real-time shear wave elastography, whose inflection point was 10.45 kPa, could predict the occurrence of hypersplenism [14]. Another study found that acoustic radiation force impulse and fibrosis-4 could be used to distinguish cirrhosis in patients with WD, which could partly replace liver biopsy [15].…”
Section: Discussionmentioning
confidence: 99%